Role of Topical Ritodrine Hydrochloride in Experimentally Induced Hypertrophic Scar in Rabbits - Kadhim, Haitham; Gatea, Fouad; Abu Raghif, Ahmed; Ali, Kholod (Iraqi Journal of Pharmaceutical Sciences, 2022)
Hypertrophic scars are fibroproliferative illnesses caused by improper wound healing, during that, excessive inflammation, angiogenesis, and differentiated human dermal fibroblast (HDF ) function contribute to scarring, whereas hyperpigmentation negatively affects scar quality. Over 100 million patients heal with a scar every year. To investigate the role of the beta 2 adrenergic receptor (β2AR); Ritodrine, in wound scarring, the ability of beta 2 adrenergic receptor agonist (β2ARag) to alter HDF differentiation and function, wound inflammation, angiogenesis, and wound scarring was explored in HDFs, zebrafish, chick chorioallantoic membrane assay (CAM), and a porcine skin wound model, respectively. A study identify a β2AR-mediated mechanism for scar reduction. β2ARag significantly reduced HDF differentiation, via multiple cAMP and/or fibroblast growth factor 2 or basic FGF (FGF2)-dependent mechanisms, in the presence of transforming growth factor betaβ1, reduced contractile function, and inhibited mRNA expression of a number of profibrotic markers. β2ARag also reduced inflammation and angiogenesis in zebrafish and CAMs in vivo, respectively. In Red Duroc pig full-thickness wounds, β2ARag reduced both scar area and hyperpigmentation by almost 50% and significantly improved scar quality. Indeed, mechanisms delineated in vitro and in other in vivo models were evident in the β2ARag-treated porcine scars in vivo. Both macrophage infiltration and angiogenesis were initially decreased, whereas DF function was impaired in the β2ARag-treated porcine wound bed. This data reveal the potential of β2ARag to improve skin scarring. The purpose of this study was to assess the therapeutic effect of topical Ritodrine hydrochloride on hypertrophic scars in rabbits. Thirty-two healthy male albino rabbits that divided in to 4 groups were included in the study (healthy; induced untreated hypertrophic scars; induced hypertrophic scars treated with 0.1% Triamcinolone acetonide (TAC) as a standard drug; and induced hypertrophic scars treated with 0.5% Ritodrine HCL gel twice daily for 21 days. Histopathology of skin sections, transforming growth factor beta1 TGFβ-1 level, and collagen III alpha1 in skin tissue were all used as outcome measures. Compared to the induced hypertrophic scar group; treatment with Ritodrine significantly reduced means of TGF β1 and collagen III (p ≤0.01); significantly reduce mean score of inflammation (p ≤0.001), significantly lowered scar size (P ≤ 0.001), and significantly lower mean scar height (P≤0.001), but no significant decrease in SEI (P>0.05). Therapy of induced hypertrophic scar with topical Ritodrine was successfully effective in rabbits. It reduced the immunological score (TGF-β1, collagen III), inflammation, and scar size in a substantial way. This effect was comparable (except in terms of SEI) to topical Triamcinolone acetonide efficacy